Pastoral Berbasis Digital Bagi Generasi Alpha di Jemaat GMIM Betania - Dulmanan, Seisy Christifasia Sukacita; Tumiwa, Evi S. E. (PT. Giat Konseling Nusantara, 2025)
This research aims to examine and analyze in-depth a digital theology-based pastoral care model as a response to pastoral challenges in the digital age. This approach goes beyond the use of technology as a mere tool, but rather integrates core theological principles such as the theology of presence, theology of embodiment, and theology of community with virtual tools and spaces. The methodology used is a qualitative literature study, analyzing key works by digital theologians such as Heidi A. Campbell and Tim Hutchings, and integrating these with pastoral practice.The results of this study demonstrate that effective digital pastoral care requires an understanding of technology as an environment, not just an instrument. This requires spiritual directors to